Evaluation of Longitudinal Strength of a Cargo Barge Based on Shear Force and Still Water Bending Moment under Various Loading Conditions: Evaluation of Longitudinal Strength of a Cargo Barge Based on Shear Force and Still Water Bending Moment under Various Loading Conditions - Budhi Santoso; Romadhoni Romadhoni; Jamal Jamal; Deny Nusyirwan; Naufal Abdurrahman; Zulfaidah Ariany (Indonesian Journal of Maritime Technology, 2026)
ABSTRACT – Longitudinal strength is a fundamental aspect of barge structural safety because variations in loading magnitude and load position may significantly affect the global hull girder response. This study aims to evaluate the longitudinal strength of a cargo barge based on shear force and still water bending moment under various loading conditions. The object of the study is a cargo barge with principal dimensions of 330 ft × 90 ft × 21 ft and a lightship weight of 1802.9 tons. The analysis was carried out using a still-water longitudinal strength approach based on the distribution of weight and buoyancy along the vessel length. Six loading conditions were investigated, namely lightship, fully loaded, partially loaded at 50%, and three crane-shift positions at the aft, midship, and fore sections. The net load distribution was obtained from the difference between distributed weight and buoyancy, and then integrated to determine the shear force and still water bending moment along the hull. The results show that the fully loaded condition produced the most critical structural response, with a maximum shear force of 0.385 × 10³ ton at Frame 50 and a maximum still water bending moment of -6.212 × 10³ ton·m at Frame 35. In contrast, the lightship condition generated the lowest internal force response. All evaluated loading conditions remained below the permissible shear force and still water bending moment limits, indicating that the barge satisfies the applicable longitudinal strength requirements. The study concludes that the vessel is structurally acceptable under all investigated loading scenarios, with the fully loaded condition representing the governing case for safe operation and load planning.